2023
DOI: 10.3390/ijms24097855
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Stress-Dependent Regulation of Na,K-ATPase in Ischemic Heart Disease

Abstract: In cardiomyocytes, regular activity of the Na,K-ATPase (NKA) and its Na/K pump activity is essential for maintaining ion gradients, excitability, propagation of action potentials, electro-mechanical coupling, trans-membrane Na+ and Ca2+ gradients and, thus, contractility. The activity of NKA is impaired in ischemic heart disease and heart failure, which has been attributed to decreased expression of the NKA subunits. Decreased NKA activity leads to intracellular Na+ and Ca2+ overload, diastolic dysfunction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 157 publications
(179 reference statements)
0
9
0
Order By: Relevance
“…Hypoxia (a hallmark feature of IHD) was used to stress hearts from male and female p62icKO mice. 82 In the p62icKO female mice, hypoxia decreased systolic function to a greater degree as compared to normoxia, an effect that was not observed in the male mice ( Figure 1 A and B ).…”
Section: Discussionmentioning
confidence: 82%
“…Hypoxia (a hallmark feature of IHD) was used to stress hearts from male and female p62icKO mice. 82 In the p62icKO female mice, hypoxia decreased systolic function to a greater degree as compared to normoxia, an effect that was not observed in the male mice ( Figure 1 A and B ).…”
Section: Discussionmentioning
confidence: 82%
“…The decreased NKA activity has been attributed to decreased expression of the subunit proteins. However, inconsistent findings from expression studies cannot substantially clarify the decreased NKA activity [2]. For instance, in a rabbit heart failure model, Bossuyt et al reported increased intracellular Na + accumulation, decreased NKA activity along with decreased protein expression of α1and α2-NKA in ventricular homogenates and isolated myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The Na,K-ATPase (NKA) pump is a member of the P-type ATPase family [1]. In the heart muscle it maintains the generation of action potentials, electrical activity, maintenance of Na + and Ca 2+ ion gradients, and cell survival [2]. Thus, proper function of the NKA is vital for cellular viability.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an increase in anaerobic glycolysis that generates lactate and causes a change in intracellular pH that drops to a value of 6.2 after about ten minutes [153]. An ionic imbalance is therefore established also due to the blockage of the Na + /K + and Na + /Ca 2+ pumps; Na + and Ca 2+ accumulate inside the cell which, combined with the accumulation of other metabolites such as lactate and protons, draws water inside the cell, causing swelling [154,155]. Reperfusion provides oxygen and allows the replenishment of substrates in the ischemic area that are essential to produce ATP, glucose, and fatty acids, all of which are important for cell survival but can also contribute to exacerbating ischemic damage.…”
Section: Ischemic Reperfusion Injurymentioning
confidence: 99%